Risk of osteoarthritis and other long-term health outcomes in former elite English cricketers - Jones, M; Davies, M; Leyland, K; Delmestri, A; Porter, A; Ratcliffe, J; Peirce, N; Newton, J; Arden, N (Elsevier, 2017)
There is a marked lack of research into the long-term health of former elite cricketers. The aim of this study is to analyse the risk of long-term health conditions in former elite cricketers by comparing the prevalence of their chronic conditions to a general population sample.